EXPLORING THE RELATIONSHIP AMONG INSTITUTIONAL INTERNAL VALUES AND STUDENTS PERFORMANCE AT HIGHER LEVEL - Dr Uzma Munawar; Marium Hussain; Husna Nazeer (International Journal of Contemporary Issues in Social Sciences, 2024)
The study investigate the relationship among institutional internal values and students performance at high level the basic purpose of the study is to explore the relationship between of intuitional values on students academic performance at higher level. The Research design adopted for the study is quantitative in nature and exploratory. The method was used cross sectional survey for better collection of data from student and faculty members. This study is descriptive in nature to find out the relationship between institutional internal values and students academic performance. The sampling technique used in research stratified random sampling technique. The sample size around of 110 faculty members and 220 students of higher level self reported questionnaire use for data collection. The data was analyze by using different statistical like mean standard, deviation frequency, distribution frequency distribution. To find out the relationship between student institutional internal values and student academic performance indicators will be tested with the pairs and correlation coefficient and multiple regression regression will be established the prediction power of various dimensions of different institutional value All students performance out come this and as will help to determine with specific behavior their most significant on student performance. The findings of the research strong positive correlation between disruptive behavior/values of students and both academic pressure and competition (r = 0.449, p<0.01) and ineffective conflict resolution (r = 0.492, p <0.01). Ineffective conflict resolution also shows a significant positive correlation with academic pressure and competition (r = 0.547, p < 0.01). Classroom environment positively correlates with teacher-student interaction (r = 0.335, p < 0.01) and peer interaction (r = 0.266, p < 0.01). Most correlations involving performance of students are weak and not statistically significant.